Rancang Bangun Pompa Hidram Untuk Menaikan Air Dari Sumber Mata Air Ke Perkebunan Penduduk - Nusyirwan; Gani Pratama; Ruzita Sumiati; Yetri, Yuli (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2025)
The hydram pump has been designed and manufactured to help people who lack water on plantation land. Hydraulic pumps are an appropriate technology in the field of pumping that use water momentum (water hammer) to raise the pumped water. The design and manufacture of hydram pumps aims to raise water from springs to residents' plantations. The specifications for making a hydram pump are 2 inches for the pump body, 3 inches for the pump air tube, with 3 valves (2 exhaust valves and 1 delivery valve). The results of test 1 at an output height (h) of 1m produced a pump output discharge of 3.12x10-4m3/s, a discharge at the exhaust valve of 7.52x10-4m3/s, and an efficiency of 19.59%. Test 2 at an output height (h) of 2.5m produced a pump output discharge of 2.08x10-4m3/s, a discharge at the exhaust valve of 7.27x10-4m3/s, and an efficiency of 36.96%. Then test 3 at an output height (h) of 5m produced a pump output discharge of 1.08x10-4m3/s, a discharge at the exhaust valve of 7.16x10-4m3/s, and an efficiency of 43.66%. The test results show that the higher the h output, the smaller the water discharge coming out of the hydram pump, and the greater the efficiency of the hydram pump.